The Relationship Between Competitive Position And Efficiency in The Indonesian-Banking Sector: A Panel Data Analysis - Aruddy, Aruddy; Achsani, Noer Azam; Wijayanto, Hari; Sartono, Bagus (Indonesian Journal of Business and Entrepreneurship, 2019)
Analysis on the relationship between competitive position and efficiency with the focus on the Indonesian commercial banks is still very rare. On the other hand, the commercial banks contains banks have systemic impact when they have troubles. The objective of this analysis is to examine the direction of the relationship between competitive position and efficiency which has managerial and policy implications for the parties concerned. The relationship was evaluated using Granger-causality test, where previous studies for Indonesian banking sector did not use this test. The quarterly financial data of each bank sample, balanced sheet and profit/loss statement, were used to calculate the efficiency score and Lerner index. The data were taken from the website of Otoritas Jasa Keuangan (OJK). Lerner index was used as an indicator for competitive position of banks, and higher index means a stronger competitive position. A score calculated by data envelopment analysis (DEA) method is a measure for bank efficiency. Dynamic model is estimated by generalized method of moment (GMM) to address endogeneity and heteroscedasticity issues. The study found that there is a significant one-way positive relationship between efficiency and competitive position, and the causality runs from efficiency to competitive position. The policy implication in this finding is that regulators should avoid implementing a regulation, which is counterproductive in strengthening bank’s ability to compete in the market. Keywords: competitive position, DEA, efficiency, Granger-causality, pricing power